Readers and Reading from Books at School in the Age of Artificial Intelligence: The End of an Era - Παπαδοπούλου, Σμαράγδα; Σπαντιδάκης, Ιωάννης; Γκούμας, Σταμάτης (Education Sciences, 2025)
This study evaluates the reading process in primary education through a case study conducted in a Greek elementary school with fifth and sixth grade students. It is part of a doctoral research project that aims to assess how multimodal texts—as precursors to artificial intelligence and virtual reality in human society—characterize an era that has long been celebrated in academic literature and increasingly supported in educational practice. The research draws on the existing language teaching framework established by the Greek Ministry of Education and follows a standard curriculum using official textbooks for teaching Greek as a first language within the Greek educational system.